Novelties in Myanmar Agapetes (Ericaceae) with an updated checklist of species from the country. Issue 4 (3rd March 2022) - Tong, Yi‐Hua; Fritsch, Peter W.; Tan, Yun‐Hong; Aung, Mu Mu; Yang, Bin; Armstrong, Kate E.
Abstract : We provide novel taxonomic information for Agapetes (Ericaceae) from Myanmar, describe the new species A. oligodonta, provide a supplemental description of the floral morphology of A. epacridea, and raise A. odontocera var. stenosepala to the rank of species. Line illustrations and photographs of living plants of A. oligodonta and A. epacridea are included, as well as an updated checklist of Agapetes from Myanmar (56 species, 9 varieties and 1 form) with discussion on the distribution of some species.